A meta-theoretical framework for organizing and integrating theory and research on motivation for health-related behavior - Williams, David M. (Frontiers in Psychology, 2023)
The concept of motivation is broad and multi-faceted. In health psychology, motivation has been conceptualized as cravings, urges or desires for unhealthy behaviors, such as consumption of alcohol, cigarettes, or calorie-dense foods; or as behavioral intentions or proximal goals for healthy behaviors, such as smoking cessation, physical activity, or condom use. Because of the differences in terminology and associated theoretical underpinnings, it is difficult to characterize the state of the science or integrate research findings on motivation for health-related behavior. The present paper introduces a metatheoretical Automatic-Reflective Motivation Framework (ARM-F) with the goals of organizing and integrating theory and research on motivation for health-related behaviors. At the first and broadest level, the ARM-F defines general motivation as a wanting or desire to do something. At the second level it distinguishes between automatic and reflective motivation types, consistent with emerging perspectives in health psychology, historical and contemporary philosophical views on desire, and dual-processing perspectives in psychology. At the third level, the ARM-F preserves the nuanced terminologies and conceptualizations within the automatic (e.g., craving, urge, desire) and reflective (e.g., behavioral intention) motivation categories. The ARM-F has potential utility for organizing and integrating theory and research on motivation for health-related behavior, with implications for future research.